The Evaluation of Company's Intangible Assets' influence for Business Value - Živilė Savickaitė (International Journal of Economic Sciences and Applied Research, 2014)
Mismeasurement of intangible assets in a company may result in high costs and loss of its competitiveness and position in the market. Conventional evaluation methods are not able to identify reliably intangible intensive business value because of such assets specificity. Therefore, the business assessment process adjustment, making it comprehensive and including the intangible asset valuation methods is a critical process that allows to evaluate companies better and increases business management efficiency and quality. The article states the importance of further scientific research in the areas of the intangible value resources, creation of business valuation, intangible assets valuation methods and models - the creation of intangible assets on the firm level and how they meet changing needs of the company's owners, capital markets investors, politicians and other interest-groups needs in the intangible intensive economy should be analysed as well as how economic systems based on intangible assets operates. Also special attention is be given to the strenghtening of the cooperation of scientific research and business. It's important to avoid a repeat of guidelines, methods, models and systems of intangible assets' measurement and business valuation methods and to eliminate its disadvantages in order to create and establish universal system for effective intangible intensive business valuation.
Keywords: D24; E22; G12; 330; intangible assets; business measurement process; models